Effect of Rest Period Duration between Sets of Repeated Sprint Skating Ability Test on the Skating Ability of Ice Hockey Players - Baron, Jakub; Gupta, Subir; Bieniec, Anna; Klich, Grzegorz; Gabrys, Tomasz; Swinarew, Andrzej Szymon; Svatora, Karel; Stanula, Arkadiusz (International journal of environmental research and public health, 2021)
The aim of this study was to determine the effects of two different rest periods, 2 min and 3 min, between consecutive sets of a repeated sprint skating ability (RSSA) test, on the skating ability of ice hockey players. Two RSSA tests, RSSA-2 and RSSA-3, were assessed on 24 ice hockey players. In RSSA-2, six sets of 3 × 80 m sprint skating, with 2 min passive recovery between two consecutive sets was allowed. In RSSA-3, the recovery period between the sets was 3 min. Average speed, average heart rate (HRaver), peak heart rate (HRpeak), blood lactate concentration ([BLa]), and rate of perceived exertion (RPE) were measured in both RSSA-2 and RSSA-3 tests. In all the sets, except set 1, the average speed of the subjects was significantly (p < 0.05) higher in RSSA-3 than the respective set in RSSA-2. Average HR and RPE were higher in RSSA-2 than RSSA-3 in most of the sets. For any given set, no difference in HRpeak was noted between RSSA-2 and RSSA-3. Post-sprint (Set 6) [BLa] was significantly (p < 0.05) higher in RSSA-3 than RSSA-2. This study concludes that the 3 min rest period is more beneficial than the 2 min rest period, for (1) increasing skating speed and (2) reducing overall cardiac workload and perceived fatigue.
Keywords: peak heart rate; Lactic Acid; rate of perceived exertion; Skating; kyselina mléčná; average heart rate; hokej; srdeční frekvence; average speed; lidé; Hockey; bruslení; odpočinek; speed decrement; Heart Rate; blood lactate concentration; Rest; Humans